Reversible conductivity recovery of highly sensitive flexible devices by water vapor. (December 2018) - Wang, Yuting; Su, Yingchun; Wang, Zegao; Zhang, Zhongyang; Han, Xiaojun; Dong, Mingdong; Cui, Lifeng; Chen, Menglin
Abstract With decreasing size of integrated circuits in wearable electronic devices, the circuit is more susceptible to aging or fracture problem, subsequently decreasing the transmission efficiency of electricity. Micro-healing represents a good approach to solve this problem. Herein, we report a water vapor method to repair microfiber-based electrodes by precise positioning and rapid healing at their original fracture sites. To realize this micro-level conducting healing, we utilize a bimaterial composed of polymeric microfibers as healing agents and electrically conductive species on its surface. This composite electrode shows a high-performance conductivity, great transparency, and ultra-flexibility. The transmittance of our electrode could reach up to 88 and 90% with a sheet resistance of 1 and 2.8 Ω sq−1, respectively, which might be the best performance among Au-based materials as we know. Moreover, after tensile failure, water vapor is introduced to mediate heat transfer for the healing process, and within seconds the network electrode could be healed along with recovering of its resistance. The recovering process could be attributed to the combination of adhesion force and capillary force at this bimaterial interface. Finally, this functional network is fabricated as a wearable pressure/ strain sensing device. It shows excellent stretchability and mechanical durability upon 1000 cycles. Wearable electronics: electrodes healable by water Wearable electronic devices are susceptible to degradation or fatigue fracture, but now the aged electrodes of the devices can be healed by simple water vapor treatment. A group of international researchers led by Prof Lifeng Cui from Dongguan University of Technology, China designs repairable microfiber-based network electrodes with high conductivity, high transparency and ultra-flexibility. The electrodes consist of polycaprolactone microfibers as healing agents and a thin conducting layer coating such as gold. The electrodes can recover the conductivity and mechanical strength after tensile failure or even cutting, which can be attributed to the adhesion and capillary force at the interface of gold and polymer. Upon embedding in PDMS elastomer, the electrodes show excellent durability of up to 1000 cycles and can be used in wearable pressure and strain sensing devices.